Dominantly Inherited Nemaline Myopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
A locus on chromosome 15q21-23 for a dominantly inherited nemaline myopathy with core-like lesions is reported in two unrelated families evaluated at University Medical Center, Nijmegen, The Netherlands.